2020
DOI: 10.3390/antibiotics9110821
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes and Perceptions of Medical Students on Antimicrobial Stewardship

Abstract: Antimicrobial Resistance (AMR) is an ongoing threat to modern medicine throughout the world. The World Health Organisation has emphasized the importance of adequate and effective training of medical students in wise prescribing of antibiotics Furthermore, Antimicrobial Stewardship (AMS) has been recognized as a rapidly growing field in medicine that sets a goal of rational use of antibiotics in terms of dosing, duration of therapy and route of administration. We undertook the current review to systematically s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 53 publications
3
22
0
Order By: Relevance
“…The current findings revealed that irrational consumption of antimicrobial drugs may be responsible for drug resistance leading to worldwide problem as understood by majority of the participants. This agrees with previous studies conducted in Greece whereby the majority of the students affirmed that antimicrobial resistance is a global problem [19]. The most preferred sources of information on the use of antimicrobial as suggested by the students were treatment guidelines followed by the official book.…”
Section: Discussionsupporting
confidence: 90%
“…The current findings revealed that irrational consumption of antimicrobial drugs may be responsible for drug resistance leading to worldwide problem as understood by majority of the participants. This agrees with previous studies conducted in Greece whereby the majority of the students affirmed that antimicrobial resistance is a global problem [19]. The most preferred sources of information on the use of antimicrobial as suggested by the students were treatment guidelines followed by the official book.…”
Section: Discussionsupporting
confidence: 90%
“…The students perceived that antibiotics are overused in hospitals they rotate in and acknowledged that inappropriate use of antibiotic causes antibiotic resistance. By having this knowledge, it is hopeful that the next prescribers and dispensers, with adequate training, will have a positive approach to antimicrobial resistance and antimicrobial stewardship policies [ 24 ]. However, interestingly, but not surprisingly, majority of the students (61%) reported that they bought antibiotics over the counter without a prescription from a doctor.…”
Section: Discussionmentioning
confidence: 99%
“…The latter highlights the need for interventions on antibiotic prescribers, including continuing education. Educational activities for prescribers should start early on in their career, as research thus far has highlighted gaps in medical training in the field [41,42]. Novel and effective training methods on all aspects of antimicrobial stewardship and antimicrobial resistance should be incorporated in the Medical Curricula worldwide.…”
Section: Discussionmentioning
confidence: 99%